Strategies for cultural assimilation of immigrants and their children social, economic, and political considerations - Chandan, Harish C. 1947- (Advances in religious and cultural studies (ARCS), 2023)
"This book presents chapters on how immigrants leaving their home country to live in a host country begin acculturation which is the process of adapting to a new culture and how there is a subtle cultural, social and political pressure on immigrants to adopt the cultural values of the host nation as well as the Immigrants unknowingly influence the host country in the areas of economics, politics and culture"--